Using SMT Engine to Generate Symbolic Automata - Madelaine, Eric; Qin, Xudong; Zhang, Min; Bliudze, Simon (Electronic Communications of the EASST, 2019)
Open pNets are used to model the behaviour of open systems, both synchronous or asynchronous, expressed in various calculi or languages. They are endowed with a symbolic operational semantics in terms of so-called “Open Automata”. This allows us to check properties of such systems in a compositional manner. We implement an algorithm computing these semantics, building predicates expressing the synchronization conditions between the events of the pNet sub-systems. Checking such predicates requires symbolic reasoning over first order logics, but also over application-specific data. We use the Z3 SMT engine to check satisfiability of the predicates, and prune the open automaton of its unsatisfiable transitions. As an industrial oriented use-case, we use so-called "architectures" for BIP systems, that have been used in the framework of an ESA project and to specify the control software of a nanosatellite at the EPFL Space Engineering Center. We use pNets to encode a BIP architecture extended with explicit data, and compute its open automaton semantics. This automaton may be used to prove behavioural properties; we give 2 examples, a safety and a liveness property.